The Concept of Merdeka Curriculum Implementation: Realizing Humanistic Islamic Education Learning - Sirait, Azyana Alda; Basri, Hasan; Ab Rahman, Zaizul (Educative: Jurnal Ilmiah Pendidikan, 2024)
The Merdeka curriculum, an innovative approach in the world of education, has become the main focus in efforts to realize more humanistic Islamic religious education learning. This research aims to determine the concept of implementing the Merdeka curriculum in the context of Islamic religious education learning and to determine the character and implications of the Merdeka curriculum in humanistic Islamic religious education learning for students. The research method used in this research is library research. Library research is a type of research where the data or material needed for research is obtained from sources in the library, such as books, encyclopedias, dictionaries, journals, magazines, and so on. The results of the research show that the concept of implementing an Merdeka curriculum for humanistic Islamic religious education learning includes: human values, empathy, student-centered concern. The characteristics of humanistic Islamic religious education learning in the Merdeka curriculum include: individual orientation, social interaction, active learning, character development, flexibility in learning, and holistic evaluation. Meanwhile, the implications of Merdeka curriculum learning in humanistic Islamic religious education learning include: more interesting learning, stronger character development, critical and creative thinking skills, healthy social interaction, development of problem  solving abilities, respect for diversity, independence in learning and relevance religion in everyday life. Based on the description above, it can be concluded that the concept of an Merdeka curriculum, students' understanding of the teachings of Islam is deepened with an emphasis on human values, empathy and social care. In addition, students will conduct humanistic learning to develop better character, including the ability to empathize and deeper social understanding so that the realization of students who are ethical and care about society.